Three-dimensional reconstruction and characterization of microscopic pore structure in tight reservoirs - Guan, Lijun; Xiong, Ting; Jiang, Qiantao (Frontiers in Earth Science, 2025)
Aiming at the characteristics of random lithology distribution, complex joint structures, low porosity and low permeability of key oil and gas blocks such as Kaiping, Baiyun, Xijiang and Huizhou in the South China Sea, a series of complete digital core collection schemes are implemented in this study to thoroughly analyze the densification mechanism of low permeability reservoirs. Advanced technologies are widely used in this scheme, including full-diameter dual-energy core CT imaging, micron-scale multi-scale CT imaging, focused ion beam scanning electron microscope (FIB-SEM) and quantitative analysis of mineral components. The integrated application of these technologies comprehensively analyzes rock samples from macro to micro scales, reveals their sedimentology, diagenesis and reservoir properties, and provides quantitative identification and characterization of rock lithology, mineral composition, pore structure and fracture system. The results show that the density of the reservoir gradually increases and tends to stabilize with increasing burial depth, while the tectonic joints within the reservoir become more developed, the porosity of the core decreases, and the pore size of the natural fractures also tends to decrease. This study quantitatively analyzed the petrophysical parameters such as lithology, porosity, fractures and minerals of the reservoirs, revealed the micro-development laws of the dominant reservoirs in the depressions in the eastern part of the South China Sea, and provided the scientific basis for the practice of oil and gas exploration and development, which is of important scientific ṣand practical application value for promoting the progress of oil and gas exploration technology.